Tinjauan Yuridis Terhadap Tindak Pidana Laporan Palsu - Jahawadan, Stephanie Mollucas; Latupeirissa, Julianus Edwin; Salamor, Anna Maria (Faculty of Law, Universitas Pattimura, 2024)
Introduction: False reports are a form of conveying false news, information, or notifications or an incident that did not occur.Purposes of the Research: The purpose of this research is to know and analyze the qualifications of a report as a criminal act of false reporting and to know and analyze the judge's legal considerations in the case of fake reports.Methods of the Research: The method used is normative juridical with the Statute Approach, Conceptual Approach and Case Approach, and uses primary, secondary and tertiary legal materials.Results of the Research: The results of this study indicate that a false report is qualified as a crime on the basis of fulfilling the elements of a crime, and the false report itself has been regulated in Article 220 of the Criminal Code. As well as the Judge's legal considerations relating to the decision Number: 60/Pid.B/2020/PN Blora is correct by handing down a decision against the defendant on behalf of Agus Jarmanto Bin Sujopo, imprisonment for 6 (six) months for the false report he made taking into account the factors Juridical and non-juridical factors in this case are aggravating and mitigating factors for the Defendant.